Flat-layered spherical lens antenna system in conditions of slant polarized feeder radiation - Ryazantsev, R. O.; Salomatov, Y. P.; Panko, V. S.; Sugak, M. I. (Proceedings (IEEE International Siberian Conference on Control and Communications. Online), 2016)
Investigation results of flat-layered spherical lens made from homogenous dielectric material under illumination of slant polarized wave are presented. Lens anisotropy behavior impact on polarization characteristics of beam pattern main lobe is shown. Results of axial ratio simulation at beam pattern maximum direction in working frequency range are given for different polarization angles of incident wave and for different scan angles.